2020
DOI: 10.21203/rs.3.rs-69939/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of circulating genetically abnormal cells using 4-color fluorescence in situ hybridization for the early detection of lung cancer

Abstract: Background Available biomarkers lack sensitivity for early lung cancer. Circulating genetically abnormal cells (CACs) occur early in tumorigenesis. To determine the diagnostic value of CACs in blood detected by 4-color fluorescence in situ hybridization (FISH) for lung cancer. Methods This was a prospective study of patients with pulmonary nodules ≤ 30 mm detected between 10/2019 and 01/2020 at four tertiary hospitals in China. All patients underwent a pathological examination of lung nodules found by imagin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Currently, routine markers for pleural effusion detection include adenosine deaminase, lactate dehydrogenase, glucose, ferritin, carbohydrate antigen 19‐9 (CA‐199), and carbohydrate antigen 125 (CA‐125) 7 ; although, their sensitivity and specificity are low. Thus, the search for reliable biomarkers that can distinguish MPE continues.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, routine markers for pleural effusion detection include adenosine deaminase, lactate dehydrogenase, glucose, ferritin, carbohydrate antigen 19‐9 (CA‐199), and carbohydrate antigen 125 (CA‐125) 7 ; although, their sensitivity and specificity are low. Thus, the search for reliable biomarkers that can distinguish MPE continues.…”
Section: Introductionmentioning
confidence: 99%
“…Previous findings have shown that a method based on the 4-color fluorescence in-situ hybridization (FISH) technique to identify circulating genetically abnormal cells (CACs) can be used to diagnose benign and malignant PNs (22,23). The diagnostic value of this method has been validated in a Chinese population (24), where an AUC of 0.823 was achieved for the diagnosis of PNs. In recent years, various blood markers have been developed for tumor liquid biopsy, and blood-based biomarkers can assist with tumor diagnosis.…”
Section: Original Articlementioning
confidence: 99%